Assessing the value of power interconnections under climate and natural gas price risks. (15th March 2015) - Pineau, P.-O.; Dupuis, D.J.; Cenesizoglu, T.
Abstract: The value of transmission capacity is hard to assess due to the presence of different issues: physics of power networks, economics of power systems and reliability criteria. Evolving supply and demand trends, however, create interest in increased transmission capacity, especially between jurisdictions with complementarities. Assessing the value of such interconnections is key in analyzing the viability of these projects. Based on a data set containing 10 years of hourly power flows and prices, daily temperature and natural gas prices, as well as climate change forecasts for 2020 and 2050, we simulate export revenues for a DC (direct current) interconnection between Quebec (Canada) and New York (US) under different natural gas price scenarios and extreme heat events. Our innovative approach, combined with an extensive data set, provides a prospective assessment of the value of new transmission projects. Our results suggest that future natural gas prices would be the main driving factor of future revenues on a transmission line, with climate change having a relatively much smaller impact on future revenues. Highlights: Electricity interconnections are key to power systems' efficiency and reliability. Their use depends on temperature and price differentials. Climate change will have impacts on temperature and electricity demand. Based on 10 years of data, we simulate an interconnection's future use and revenue. We find that natural gas prices drive its value, not extreme heat forecasts.